Thermodynamic evaluation of two portable cooler running with reciprocating and mini-rotary compressors - Marchi, D.; Hermes, C. J. L. (Revista de Engenharia Térmica, 2022)
Small-capacity refrigeration has got an increasing attention of the consumer market. In addition to the efficiency of electric equipment, the demand for compactness has also become a relevant requirement. Among the alternatives available to cool down small cabinets, mechanical vapor compression refrigeration remains prominent due to its satisfactory performance when compared to other cooling technologies. Compressor industries have invested in the development of compact and efficient products, exploring different compression principles for small-capacity applications, as is the case of mini-rotary compressors. In this context, the objective of the present work is to assess the thermodynamic performance of a 38-liter portable vapor compression refrigeration system running with two different compressors designed for small-capacity applications: minirotary and reciprocating. Experimental tests were carried out at three different ambient temperatures (16, 25 and 32 °C) in order to obtain the key performance parameters for each compressor (e.g., power consumption, cooling capacity, internal air temperature, and the condensing and evaporating temperatures). Finally, thermodynamic analyses were conducted to account for the internal and external irreversibilities by means of second law efficiencies, allowing for a comparison of the system performance running with both compressors in the same thermodynamic grounds. Albeit a refrigeration (second law) efficiency by 25% higher was observed for the reciprocating compressor, it provided a smaller cooling capacity and, therefore, led to a higher pull-down time.